THE INFLUENCE OF FINANCIAL KNOWLEDGE, FINANCIAL SELF-EFFICACY AND LOCUS OF CONTROL ON ISLAMIC FINANCIAL BEHAVIOR IN GENERATION IN DKI JAKARTA - Pahlevi, Muhammad Reza; Gusniarti, Gusniarti (Ekonomi Islam, 2024)
This study aims to determine the effect of Financial Knowledge, Financial Self-Efficacy, and Locus of Control both partially and simultaneously on Islamic Financial Behavior in Generation Z in DKI Jakarta. This type of research is quantitative with a causality approach. The method used in sampling is purposive sampling. The partial test shows that the financial knowledge variable has a positive and significant effect on Islamic financial behavior, financial self-efficacy has a positive and significant effect on Islamic financial behavior, and locus of control has a positive and significant effect on Islamic financial behavior. The results of this study  indicate that financial knowledge, financial self-efficacy, and locus of control simultaneously have a positive and significant effect on Islamic financial behavior.